JÁ VEJO ELE NOS QUADRINHOS: UMA ANÁLISE EM TEMPO REAL DA VARIAÇÃO DO OBJETO DIRETO ANAFÓRICO DE TERCEIRA PESSOA EM REVISTAS DA TURMA DA MÔNICA - Zanellato, Carolina Amorim (2021)
For Variationist Sociolinguistics (LABOV, 2008 [1972]), language is a heterogeneous system, being a variation inherent to the system. Omena (1978), when studying the filling of the anaphoric direct object of third person, observed a decrease in the clitic pronoun and an increase in the empty category, in addition to occurrences of pronouns in the straight case. Duarte (1986) observed that, besides to these variants, there is also an increase in anaphoric noun phrases in this function. Based on these results, the present work intends to investigate how the variation of the direct anaphoric object of third person occurs in magazines of Turma da Mônica. The study of comic books is considered important, as they are a discursive genre close to orality, in which narratives often occur through dialogues between the characters. To that end, we used the methodological construct of real time and analyzed it in different diachronies, since 1970, the initial date of publication, until the decade of 2010. Our results corroborate those of the previously mentioned researches: there is a low drop in the use of clitic – whose frequency in 1970 was 54.5% and changes to 2.5% in 2010 – the appearance of the lexical pronoun, which occurred only 3 times in 1970 and accounts for 15.7% of the total data in the last analyzed synchrony, in addition to the increase in the empty category and the noun phrase, the latter is the most common variant in our corpus. There is conclusion, therefore, that the filling of the anaphoric object in the magazines of Turma da Mônica is similar to the results found by other researchers in PB, with the substitution of the clitic pronoun by other strategies, with some essential variables for the choice of forms, such as the distance between the referent and the consequent, the animacity of the antecedent and the syntactic structure of the sentence, in addition to the year of publication of the comic strip.